Effects of alloying elements on elastic properties of Al by first-principles calculations - Wang J.; Du Y.; Shang S.L.; Liu Z.K.; Li Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effects of alloying elements (Co, Cu, Fe, Ge, Hf, Mg, Mn, Ni, Si, Sr, Ti, V, Y, Zn, and Zr) on elastic properties of Al have been investigated using first-principles calculations within the generalized gradient approximation. A supercell consisting of 31 Al atoms and one solute atom is used. A good agreement is obtained between calculated and available experimental data. Lattice parameters of the studied Al alloys are found to be depended on atomic radii of solute atoms. The elastic properties of polycrystalline aggregates including bulk modulus (B), shear modulus (G), Young’s modulus (E), and the B/G ratio are also determined based on the calculated elastic constants (cij’s). It is found that the bulk modulus of Al alloys decreases with increasing volume due to the addition of alloying elements and the bulk modulus is also related to the total molar volume (Vm) and electron density (nAl31x) with the relationship of nAl31x=1.0594+0.0207√B/Vm. These results are of relevance to tailor the properties of Al alloys.